Pemanfaatan Tomat Dalam Pembuatan Nata De Tomato - Dewi Rofita; Maria Fatima Mardina Angkur; Yohana Enda Putri (LPPM Politeknik Pratama, 2023)
Tomato is a perishable and perishable fruit, so there is a need for other alternatives for its utilization. The alternative is a food product in the form of nata (Nata De Tomato). Nata is obtained from fermentation by the bacterium Acetobacter xylinum. Tomatoes contain carbohydrates as a substrate for forming nata. The purpose of this study was to determine the effect of using tomatoes on the thickness, weight, and fiber content of the nata layer. The research design used is factorial design with 3 variables and 2 levels. In this study, the fixed variables were used, namely the volume of the media 650 ml, the fermentation temperature of 30 ºC and the concentration of the starter (10% of the fermentation medium). While the changing variables were sugar concentration (5% and 8%), acidity level (3 and 5) and fermentation time (12 and 14 days). The observed aspect is the amount of yield of each variable. The results showed that the variable data that had an effect were sugar concentration, acidity level and fermentation time. Optimal conditions at a sugar concentration of 5%, pH = 3 and fermentation time is 14 days with a yield of 60.18%. While the chemical test results obtained in the form of a carbohydrate content of 7.25%; protein content 0.11%; 1.96% sucrose content and 97.20% water content.